INTERVENTIONS TO COMBAT LONELINESS FOR OLDER ADULTS: A REVIEW OF REVIEWS. (16th November 2018) - Victor, C
Abstract: Loneliness is concept that is associated with later life and there is a considerable investment in both North America and Europe in interventions to combat loneliness. We undertook a review of reviews to identify effective interventions to alleviate loneliness in adults and included systematic reviews conducted on loneliness between 2008–2018. Unpublished grey literature published between 2008–2018 and in the form of evaluation reports is also included. We report the findings from studies using controlled study designs and measuring loneliness as reported in the source reviews. After duplicates were removed, the electronic searches returned 364 published reviews for screening, 14 of which meet our inclusion criteria. These reviews yielded 40 papers and 4658 participants all of whom were older adults (aged 55+). Studies were undertaken in a range of countries including The United States, the United Kingdom (England, Northern Ireland, Scotland, Wales), the Netherlands. Finland, Japan, New Zealand, Sweden and Taiwan. Interventions in the included studies varied and included animal interventions, technology of many kinds, gardening, physical activity, reminiscence therapy, befriending, residential and school-based camps. Delivery took place in community and care home contexts but few of the source reviews provided details of the content of the intervention and its, duration, intensity and frequency. Study quality was generally low. Interventions were poorly described in terms of content, duration, frequency and intensity. Sample sizes were small (mean = 125) and post-intervention follow-up rare. Results from controlled study designs in both community settings and care homes showed no effect of interventions on loneliness.